Alih Kode dan Campur Kode pada Film Yowes Band 3 Karya Bayu Skak dan Fajar Nugros - Sintia Haryani; Syarif Hidayatullah (FKIP, Universitas Palangka Raya, 2024)
Events of changing and merging languages often occur in films. Therefore, the researcher aims to find out the code switching and code mixing contained in the film Yowes Band 3 by Bayu Skak and Fajar Nugros. This research applies descriptive qualitative methods through the validity checking technique by listening and writing. The results of the study stated that there were 71 code switching and code mixing which were described as follows: 1) 15 Inward code switching, 2) 2 External code switching, 3) 27 Internal code mixing, 4) 27 External code mixing. The reason for deciding the object of code-switching and code-mixing is because it has a variety of languages in the Yowes Band 3 film to be the development of language knowledge for further research.